Using smartwatches for fitness and health monitoring: the UTAUT2 combined with threat appraisal as moderators. Issue 3 (17th February 2021) - Beh, Phaik Khee; Ganesan, Yuvaraj; Iranmanesh, Mohammad; Foroughi, Behzad
ABSTRACT: Recent advancements in smartwatch technology have led to several applications in continuous fitness and health monitoring. Considering the benefits of smartwatches, their low level of usage for fitness and health monitoring purposes, and the limited understanding of determinants of their usage, this study advances the body of knowledge by developing an innovative and comprehensive research model that integrates the extended unified theory of acceptance and use of technology (UTAUT2) with perceived vulnerability and perceived severity as moderators. The model was tested using partial least squares (PLS), in a quantitative study with data from 271 respondents from Malaysia. The results showed that performance expectancy, effort expectancy, facilitating conditions and hedonic motivation have positive impacts on behavioural intentions towards using smartwatches for health and fitness monitoring. Perceived vulnerability moderates positively the impacts of effort expectancy. Perceived abstract severity moderates positively the impacts of social influence and negatively the influence of hedonic motivation. The findings provide useful insights for smartwatch technology developers, marketers and managers in developing more effective devices and strategies and consequently promoting smartwatches as health monitoring devices. These outcomes extend the UTAUT2 and provide new insights into drivers of the use of smartwatches for fitness and health monitoring.